Islamic Social Finance and Environmental Sustainability: A Critical Review of Policy and Practice - Fahmi, Rizqi Anfanni (Iqtishodiah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This paper explores the integration of Islamic Social Finance (ISF) with environmental sustainability, aiming to evaluate the potential and challenges of using Islamic financial tools like zakat, waqf, and sukuk to support green projects. The research employs a narrative literature review methodology, analyzing over 200 studies, and categorizing them by thematic areas such as the role of Islamic finance instruments in sustainability, the incorporation of Environmental, Social, and Governance (ESG) principles, and the barriers to effective implementation. Key findings indicate that ISF can play a significant role in addressing sustainability goals, particularly in funding renewable energy, climate change mitigation, and social development projects. However, the study also highlights several challenges, including regulatory inconsistencies, lack of awareness among stakeholders, and insufficient institutional capacity. Additionally, the integration of Maqasid al-Shari’ah principles with modern sustainability frameworks has been proposed as a way to enhance the ethical alignment of ISF with environmental goals. Despite these opportunities, the paper points out that regulatory gaps and the limited understanding of ISF’s potential for environmental impact are major barriers. The study concludes that enhancing regulatory frameworks and promoting the use of technology, such as blockchain and fintech, can improve the transparency, accountability, and effectiveness of ISF tools. The findings provide valuable insights into how Islamic finance can support sustainable development, while suggesting further empirical research to evaluate ISF’s real-world impact and potential for scaling green finance initiatives.